Seroprevalence of brucellosis among dairy farm workers in Mexico - Miguel E Cervera-Hernández; Anabel Ordaz-Vázquez; Pedro Torres-González; Bárbara Chávez-Mazari; Orbelin Soberanis-Ramos; José Sifuentes-Osornio; Alfredo Ponce de León; Miriam Bobadilla-del Valle (Instituto Nacional de Salud Pública, 2016)
Objective. To describe the seroprevalence and associated factors for brucellosis among dairy farm workers. Materials and methods. We performed a secondary analysis of a data set and sera from a previous cross-sectional study in a dairy farm. Sera were tested for Brucella spp. antibodies by the slide agglutination test. Seropositivity was defined as a titer ≥1:40; recent infection was titers ≥1:160. Results. We tested 331 human sera. Seroprevalence of brucellosis was 18.1% (60/331; 95% CI 14.1-22.7); 13.3% of them (8/60; 95% CI 5.9 - 24.5) corresponded to recent infection. Highexposure occupation (calf caretaker; OR 3.3; 95%CI 1.1 - 9.7), daily hours in contact with cows (OR 1.1; 95%CI 1.03 - 1.2), and living on-site (OR 2.2; 95% CI 1.1 - 4.4) remained inde- pendently associated with seropositivity. Conclusions. We found a high seroprevalence of brucellosis among dairy farm workers, as well as a significant association among those with prolonged and close contact with cattle.